Quality assurance in higher education pilot in Al-Mansour University College (Al-Mansour Journal, 2023)
Many of the Arabian universities are sustaining from the weakness of their documentation and the assurance methodology of their academic quality, in addition they don’t reliance on an international academic standards to measure their learning outcomes quality, that ‘s why they can’t prove the quality of the outcomes.This research is trying to identify the basic concepts of the academic quality assurance in higher education with a presentation of a pilot study in Al-Mansour University College learning on a questionnaire designed especially to this research and a statistical analysis to the questionnaire outcomes. Finally the research presented a list of conclusions and recommendation